2017
DOI: 10.1016/j.atmosenv.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partitioning and oxidative processing of PAH in fogs and clouds on atmospheric lifetimes of PAH

Abstract: The importance of the atmospheric aqueous phase of fogs and clouds, for the processing and removal of polycyclic aromatic hydrocarbons (PAHs) is not well known. A multiphase model was developed to determine the fate and lifetime of PAHs in fogs and clouds for a limited set of daytime conditions. The model describes partitioning between three phases (aqueous, liquid organic, and gas), experimental and estimated (photo)oxidation rates. Using a limited set of microphysical and chemical input conditions, the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…64 In addition, because of discontinuity and much shorter durations of rainfall, wet deposition is considered to be at least 10 times less contribution to PAHs in the air−water interface than dry deposition. 65 Therefore, examining the combined impacts of free air−water exchange and dry deposition (F a/w+d ), the transport fluxes of PAHs at the air− water interface in the central TWS showed significant differences with the JRDW and SCSWC (Figure 3d). In the central TWS, the transport of 3-and 4-ring PAHs across the air−water interface were dominated by volatilization and deposition processes, respectively, based on the F a/w values of these PAHs (Figure 3c,d).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…64 In addition, because of discontinuity and much shorter durations of rainfall, wet deposition is considered to be at least 10 times less contribution to PAHs in the air−water interface than dry deposition. 65 Therefore, examining the combined impacts of free air−water exchange and dry deposition (F a/w+d ), the transport fluxes of PAHs at the air− water interface in the central TWS showed significant differences with the JRDW and SCSWC (Figure 3d). In the central TWS, the transport of 3-and 4-ring PAHs across the air−water interface were dominated by volatilization and deposition processes, respectively, based on the F a/w values of these PAHs (Figure 3c,d).…”
Section: Resultsmentioning
confidence: 97%
“…In the JRDW, that was because of the local higher particulate PAH discharge in the atmosphere; but in the SCSWC, that could be due to the higher loadings of PAHs on the fine particulates with larger specific surface areas in the long-range transport of SCSWC . In addition, because of discontinuity and much shorter durations of rainfall, wet deposition is considered to be at least 10 times less contribution to PAHs in the air–water interface than dry deposition . Therefore, examining the combined impacts of free air–water exchange and dry deposition ( F a/w+d ), the transport fluxes of PAHs at the air–water interface in the central TWS showed significant differences with the JRDW and SCSWC (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are toxic molecules. These pollutants are ubiquitous in environmental and atmospheric aqueous phases including surface waters, fog and cloud droplets, and particulate matter. Photooxidation is a common fate of PAHs in environmental and atmospheric waters. Since products are often even more toxic than the parent compounds, accurate photooxidation kinetics are needed in order to predict the health effects of PAHs .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, as the first layer at the lung/air interface, airway surface liquid (i.e., lung lining fluid above the membranes of the epithelial cells) can more easily host the process of oxidation of O 3 and CC bond-containing compounds due to its higher temperature (32–37 °C) compared with the temperature of air . Laboratory research has shown that the kinetic rate constants of aromatics, such as acenaphthene and phenanthrene, in the liquid phase increased by 3–4 orders of magnitude compared with those in the gas phase at 25 °C and pH 7. Leveraging the neutral pH of EBC (7.9 ± 1.1) in the airways in our study, we found the relevant oxidation processes follow two major pathways: direct reaction with O 3 and indirect reaction with reactive oxygen species (e.g., hydroxyl radicals) produced through O 3 decomposition. Therefore, we speculate that inhaled active compounds, namely, aromatics and terpenoids, are predisposed to oxidation by O 3 , resulting in the formation of toxicologically functional groups (e.g., carbonyl groups) in the body .…”
Section: Resultsmentioning
confidence: 99%